Penerapan Permainan Kreatif Mencari Harta Karun Untuk Meningkatkan Kemampuan Memecahkan Masalah Pada Anak Kelompok B Di Taman Kanak-Kanak - Setyowati, Mm Novita Dwi (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2018)
The aspect of cognitive development in solving problems is a major aspect that must be developed in early childhood, since the child's age in seeking new experiences is always related to his thinking ability. Children learn through play activities, through the application of creative games to find treasures in learning can improve thinking skills in solving problems in children, because this game is a game of merging from searching for traces (maze) and puzzle. Research purposes Describe the application of Creative Game Finding Treasure for improve problem solving skills in group B children in TK Negeri Pembina Kota Kediri. The methods used in this research are: (1) Classroom Action research design, through (a) planning stage, (b) Implementation stage, (c) Observation of activities, (d) Reflection; (2) Background and research subject of child group B in TK Negeri Pembina Kota Kediri with the number of students 20 children; (3) Technique of collecting data in this research is from process observation, documentation, test; (4) The research instrument uses the design of daily activities, scenarios, media, and assessment sheets; (5) The data analysis in this research uses mean calculation formula which refers to child activeness and success of children on the application of creative game looking for treasure. Result from research of creative game game looking for treasure to improve problem solving ability in child in kindergarten. City Pembina City Kediri done with two cycles where each cycle consists of two meetings. From the results of research can be concluded that the application of creative games to find treasure can improve the ability to solve problems in children group B TK Negeri Pembina Kediri.